Urine proteomics in the diagnosis of stable angina. Issue 1 (December 2016) - Neisius, Ulf; Koeck, Thomas; Mischak, Harald; Rossi, Sabrina; Olson, Erin; Carty, David; Dymott, Jane; Dominiczak, Anna; Berry, Colin; Oldroyd, Keith; Delles, Christian
Abstract Background We have previously described a panel of 238 urinary polypeptides specific for established severe coronary artery disease (CAD). Here we studied this polypeptide panel in patients with a wider range of CAD severity. Methods We recruited 60 patients who underwent elective coronary angiography for investigation of stable angina. Patients were selected for either having angiographic evidence of CAD or not (NCA) following coronary angiography (n = 30/30; age, 55 ± 6 vs. 56 ± 7 years, P = 0.539) to cover the extremes of the CAD spectrum. A further 66 patients with severe CAD (age, 64 ± 9 years) prior to surgical coronary revascularization were added for correlation studies. The Gensini score was calculated from coronary angiograms as a measure of CAD severity. Urinary proteomic analyses were performed using capillary electrophoresis coupled online to micro time-of-flight mass spectrometry. The urinary polypeptide pattern was classified using a predefined algorithm and resulting in the CAD238 score, which expresses the pattern quantitatively. Results In the whole cohort of patients with CAD (Gensini score 60 [40; 98]) we found a close correlation between Gensini scores and CAD238 (ρ = 0.465, P < 0.001). After adjustment for age (β = 0.144;P = 0.135) the CAD238 score remained a significant predictor of the Gensini score (β =0.418;P < 0.001). In those with less severe CAD (Gensini score 40 [25; 61]), however, we could not detect a difference in CAD238 compared to patients with NCA (−0.487 ± 0.341 vs. −0.612 ± 0.269, P = 0.119). Conclusions In conclusion the urinary polypeptide CAD238 score is associated with CAD burden and has potential as a new cardiovascular biomarker.